Evolution of Homeobox Gene Clusters in Animals: The Giga-Cluster and Primary vs. Secondary Clustering - Ferrier, David E. K. (Frontiers in Ecology and Evolution, 2016)
The Hox gene cluster has been a major focus in evolutionary developmental biology. This is because of its key role in patterning animal development and widespread examples of changes in Hox genes being linked to the evolution of animal body plans and morphologies. Also, the distinctive organisation of the Hox genes into genomic clusters in which the order of the genes along the chromosome corresponds to the order of their activity along the embryo, or during a developmental process, has been a further source of great interest. This is known as Colinearity, and it provides a clear link between genome organisation and the regulation of genes during development, with distinctive changes marking evolutionary transitions. The Hox genes are not alone, however. The homeobox genes are a large super-class, of which the Hox genes are only a small subset, and an ever-increasing number of further gene clusters besides the Hox are being discovered. This is of great interest because of the potential for such gene clusters to help understand major evolutionary transitions, both in terms of changes to development and morphology as well as evolution of genome organisation. However, there is uncertainty in our understanding of homeobox gene cluster evolution at present. This relates to our still rudimentary understanding of the dynamics of genome rearrangements and evolution over the evolutionary timescales being considered when we compare lineages from across the animal kingdom. A major goal is to deduce whether particular instances of clustering are primary (conserved from ancient ancestral clusters) or secondary (reassortment of genes into clusters in lineage-specific fashion). The following summary of the various instances of homeobox gene clusters in animals, and the hypotheses about their evolution, provides a framework for the future resolution of this uncertainty.